A Jurisprudential Review of the Application of Monetary Punishment for the Circulation of Illegal Cigarettes - Rispandi, Ade Endang; Arif Rahman Hakim Syadzali (Syariah: Journal of Fiqh Studies, 2025)
Indonesia plays a significant role in minimizing the negative impact of large-scale illegal tobacco production. Legislation imposing fines is expected to serve as a solution to address concerns regarding its effects on public health and the economy. However, the imposition of fines is claimed to violate maqāṣid asy-syarī‘ah and even the consensus (ijmā‘) of Islamic scholars. This study aims to analyze the extent of Islamic perspectives on the imposition of fines, particularly in Indonesia. This study employs library research using a qualitative approach. The research findings indicate that the imposition of monetary fines (ta‘zīr bi al-māl) is not considered valid unless under circumstances of necessity (ḍarūrah), according to the consensus of the four major Islamic schools of thought (madzāhib). However, fines in the form of asset destruction directly related to the offense (ta‘zīr fī al-māl) are deemed permissible according to the Mālikī school of thought. The implications of this study suggest that the government must ensure the presence of an urgent necessity to justify the legislation of fines, apply proportionality in assessing the need, and guarantee that the allocation of collected fines is accurately directed toward the public interest.